2022
DOI: 10.3390/ijerph19169908
|View full text |Cite
|
Sign up to set email alerts
|

Does Body Position Influence Bioelectrical Impedance? An Observational Pilot Study

Abstract: As the availability of various bioelectric impedance analysis (BIA) tools is increasing, the patient’s position during the test may be of significant importance for the comparability of the results. An observational pilot study was undertaken between March and May 2021 at the Center for Innovative Research in Medical and Natural Sciences at the University of Rzeszow, Rzeszów, Poland. All participants (n = 49: M: 21.05 y ± 1.12 vs. F: 21.34 y ± 2.06) were subjected to measurements of selected nutritional status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It is necessary to consider the position in which the impedance measurement is performed. Wiech et al ( 60 ) demonstrated differences between measurements in the lying, sitting, and standing positions, and they analyzed their data by considering sex. In men, there was a significant difference in PhA when it was measured in the sitting position (7.23 ± 1.40) compared with the standing position (6.27 ± 0.68) ( p = 0.020).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to consider the position in which the impedance measurement is performed. Wiech et al ( 60 ) demonstrated differences between measurements in the lying, sitting, and standing positions, and they analyzed their data by considering sex. In men, there was a significant difference in PhA when it was measured in the sitting position (7.23 ± 1.40) compared with the standing position (6.27 ± 0.68) ( p = 0.020).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that PhA measurements can vary according to the measuring device and body position at the time of assessment (standing vs. supine) [ 44 ]. During this research, all measurements were made standing to avoid variance.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the Inbody 770 device as a meter is validated against the gold standard DEXA with 98% correlation [ 43 ]. The measurements were taken standing up because research has shown that position from which the PhA is taken interferes with some of the values, so the way in which the bioimpedance was measured should always be known [ 44 ]. The PhA is compounded by two elements: the reactance (X) and the resistance (R).…”
Section: Methodsmentioning
confidence: 99%
“…Disposable electrodes (Biatrodes, Pontassieve, Fl, Italy: single electrode impedance -25-30 Ω, compliance with Directive 93/42/ECC and ISO 10993-1:2003) were placed on the dorsal surface of the upper limb (wrist joint) and lower limb (ankle joint). All measurements were performed according to guidelines described by other authors [19][20][21][22][23]. Measurements were taken by a medic with experience in the method.…”
Section: Methodsmentioning
confidence: 99%